2002
DOI: 10.1089/088922202753614191
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Replication-Competent HIV Type 1-Infected Circulating Monocytes from Individuals Receiving Antiretroviral Therapy

Abstract: The affect of antiretroviral therapy (ART) on HIV-1 recovery from blood monocytes was determined in purified peripheral blood monocyte-derived macrophage (MDM) cultures from HIV-1-infected subjects with undetectable plasma viremia or active viral replication. Additionally, the association between replication-competent HIV-1-infected MDM and neurocognitive status was examined. Fifty-two individual with previous AIDS-defining illnesses receiving nucleoside analogues with and without protease inhibitors or no ART… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
0
10
0
2
Order By: Relevance
“…Clinical data have shown that despite an HIV-1 viral load below the limit of detection in patients with HIV/AIDS treated with ART, HIV-1 infected Mfs are found in the tissues, and proviral DNA can be detected in Mfs [5,25]. Importantly, susceptibility to infection in individuals with HIV-1/AIDS is likely a consequence of defective AM innate immune functions, including phagocytosis, intracellular killing, and inflammatory cytokine production [24,26].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data have shown that despite an HIV-1 viral load below the limit of detection in patients with HIV/AIDS treated with ART, HIV-1 infected Mfs are found in the tissues, and proviral DNA can be detected in Mfs [5,25]. Importantly, susceptibility to infection in individuals with HIV-1/AIDS is likely a consequence of defective AM innate immune functions, including phagocytosis, intracellular killing, and inflammatory cytokine production [24,26].…”
Section: Discussionmentioning
confidence: 99%
“…They are able to cross the blood-tissue barriers and can transfer HIV to all tissues and organs. It has also been reported that the macrophages isolated from patients receiving ART harbour replication competent HIV [ 72 ]. These findings indicate that the infected macrophage, are of critical importance in HIV pathogenesis contributing to early-stage cell-to-cell viral transmission, dissemination and persistence throughout the body.…”
Section: Macrophages Plasticity and Polari-zation In Hiv Infectionmentioning
confidence: 99%
“…Monocytes are targets of HIV infection as they express the CD4 receptor and chemokine co-receptors for HIV entry. However, both in vivo and in vitro data suggest infection of circulating monocytes with HIV to be rare in comparison to CD4 T cell compartments [ 72 - 74 ], which is often latent and could lead to productive infection during differentiation into macrophages. Later on, sophisticated approaches using in situ hybridization coupled with simultaneous surface immuno-phenotyping revealed a higher level of monocyte infection and demonstrated the production of viral mRNA in these cells indicating productive infection [ 75 , 76 ].…”
Section: Circulating Monocytes and Hiv Infection: An Underrated Inflamentioning
confidence: 99%
“…A study on the effect of HAART on HIV-1 recovery from purified peripheral blood monocyte-derived macrophages showed that circulating monocytes constitute a significant source of replication-competent virus in HAART naive HIV patients and in HIV patients failing HAART (44). Moreover, a study by Lanier et al describing evolutionary relationships between the HIV-1 reverse transcriptase from multiple anatomical compartments of a patient enrolled in a phase III trial designed to assess the efficacy of ABC in subjects with HAD, reports compartmentalized evolution in the midfrontal gyrus of the brain and suggest that incomplete drug penetrance into this region may in part be responsible (47,65).…”
Section: Resistance Compartmentalization and Immune Reconstitutionmentioning
confidence: 99%